A new gigantic species of Zeidora Adams, 1860 from Antarctic waters (Gastropoda: Fissurellidae) - Aldea, Cristian (2011)
A new species of Zeidora, Z. antarctica new species, is described from Bellingshausen Sea, Antarctica. The species is characterized by having a large and low shell, with delicate shell sculpture, spire extending beyond the shell’s outline, and relatively wide septum, curved at the anterior margin.